Strategi Pendidikan Inovatif Untuk Keterampilan Global Dalam Konteks Generasi Emas 2045 - Abdul Rahman Bintang; Restu Permohonan Hasibuan; Muhammad Fadhel; Ahmad Sabri; Rully Hidayatullah (Journal of Regional Development and Technology Initiatives, 2024)
This research aims to explore innovative educational strategies necessary to strengthen global skills in the 2045 Golden Generation. Through an in-depth analysis of the dynamics of social, technological, and global economic complexities, the article identifies substantial challenges in preparing the next generation for a rapidly changing world. Within this context, the study highlights the urgency for a profound transformation in the education system to integrate essential and relevant skills aligned with an increasingly interconnected and diverse world. The research suggests that project-based learning, leveraging advanced technology, and enhancing cross-sectoral collaboration are key to addressing these challenges. Through appropriate technology integration, new opportunities arise to facilitate more adaptive and responsive learning tailored to individual student needs. Furthermore, close collaboration among formal education, industry, and community institutions can provide more contextual and relevant learning experiences. By offering concrete solutions, this research not only provides deep insights into the complexity of challenges facing education but also depicts the transformative potential of innovative education in shaping an inclusive, dynamic, and highly competitive education future. Therefore, this research is relevant to education academics and practitioners and policymakers, industry stakeholders, and the broader community concerned with sustainable and inclusive future development.